THE The Impact of Procuring Per Offer, Turnover of Absolute Resource, Return on Value and Debt Asset Ratio on Offer Value of Maufactur Area Recorded on the Indonesia Stock Trade Period 2019 - 2022 - Marselia Purnama; Octavianti Purnama (eCo-Buss, 2023)
The value of the money is going to decrease because of inflation, so we have to invest in an investment asset. The investment tool explored in this research is c-stock which uses financial ratios to determine whether financial ratios are correlated with stock prices in order to identify capital intensive companies. This research uses ratios such as EPS TATO ROE and asset or debt ratio to provide profitability. This study has been carried out in the case of manufacturing companies listed on IDX, using Eviews version 10 as a data processing tool. The primary sampling method was applied in this study, as it is the standard of sampling. From 2019 to 2022 the samples were six companies with research data and therefore 32 observation reports have been collected. Because of the review, it is known that (1) Profit per share emphatically affects stock costs. The meaning of 00154 demonstrates this so H1 is acknowledged. ( 2) The complete resource turnover rate essentially affects the stock cost as confirmed by the meaning of 01040 so H2 is dismissed. ( 3) Return on value emphatically affects stock cost ( ) which is demonstrated at the importance level 00390 so H3 is acknowledged. ( 4) The obligation to resource rate affects share costs, this is validated by a critical worth of0.0719 so H4 is dismissed;( 5) accomplished contemporaneous Experimental outcomes calculation results F of3.103040 with probability0.031819 can be closed in the event that all factors have a huge impact contemporaneously on costs of stock. The aftereffects of the retrogression examination show the adjusted worth( r2) of0.213441, implies that varieties in Profit per Offer, Advancement of All out Resource, Return on Value, and Obligation to implies rate can make sense of the21.34 of changes in stock value, the remaining78.66 is made sense of not analyzed by different factors in this review.